ORIENTAÇÃO ESPACIAL: APLICAÇÃO DA SINTAXE ESPACIAL COMO METODOLOGIA DE ANÁLISE EM CAMPUS UNIVERSITÁRIO - Mano, Cássia; Braga, Andrea (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The aim of this paper is to investigate the effects of urban configuration on a campus in the city of Porto Alegre / RS, concerning wayfinding for its users. The hypothesis to be verified is the following: the greater the distance between buildings, which results in the predominance of residual spaces without use, the greater the difficulty of wayfinding. It is assumed that when people are disoriented, they tend to choose more integrated areas for displacement, those that are domain of the visitor/strange, instead of the segregated areas, whose control belongs to the resident/user familiar with the space. The analysis held on Campus Center of UFRGS / RS - Brazil. Space Syntax measures were used to analyse the urban configuration, considering the axial map of the pedestrian routes towards the main entrances of the buildings. In addition, data collection included physical measurements and observation map as a complementary method. The main results indicate that a higher integration of the configuration system tends to facilitate the wayfinding for its users.